PENGARUH BUDGET PARTICIPATION, SELF ESTEEM DAN BUDGET EMPHASIS TERHADAP BUDGETARY SLACK PADA HOTEL BERBINTANG DIKOTA DENPASAR - Ni Putu Diah Rusmawati (UNHI Press, 2021)
This study aims to determine the effect of Budget Participation, Self Esteem and Budget Emphasis on the Budgetary Slack at Star Hotels in Denpasar City. The place where this research was conducted at the Star Hotels in Denpasar City. The data used are primary data using a questionnaire. The population in this study is 16 hotels located in Denpasar City at PHRI Bali, 2020. The method of determining the sample used in this study is to use purposive sampling technique with a total sample of 174 Departement Heads. The data collection techniques used were observation, interviews and questionnaires. While the analyzing technique used is regression analysis. This study resulting an indicate that Budget Participation effecting the Budgetary Slack with positively. Self Esteem has a negative and significant effect on the Budgetary Slack variable. Budget Emphasis has a positive and significant effect on the Budgetary Slack variable.